GIS applications for mapping and spatial modeling of urban-use water quality: a case study in District of Cuiabá, Mato Grosso, Brazil Aplicações de SIG para mapeamento e modelagem espacial da qualidade de água para uso urbano: estudo de caso num distrito de Cuiabá, Mato Grosso, Brasil - Peter Zeilhofer; Liliana Victorino Alves Corrêa Zeilhofer; Edna Lopes Hardoim; Zoraidy Marques de Lima; Catarina Silva Oliveira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
A cross-sectional study utilizing spatial analysis techniques was conducted to study water quality problems and risk of waterborne enteric diseases in a lower-middle-class urban district of Cuiabá, the capital of Mato Grosso State, Brazil. Field surveys indicate high rates of supply water contamination in domiciles and, conspicuously, in public and private schools. Logistic regression models developed for the variables turbidity, Escherichia coli, total coliforms, and intestinal parasite infection did not identify singular explanatory factors for the supply water conditions and elevated incidences of enteric diseases among children. The contamination problems were found to be the result of precarious conditions involving both public infrastructure and in-building sanitary installations and their maintenance. GIS methods were successfully applied to create spatial datasets for logistic regression model building and to construct risk maps using regression coefficients. Foi realizado um estudo transversal incluindo técnicas da análise espacial para avaliar problemas de qualidade de água de consumo e riscos de doenças entéricas em um bairro da classe média baixa na cidade de Cuiabá, capital de Mato Grosso, Brasil. Os trabalhos de campo indicam altos índices de contaminação nos domicílios e, particularmente, nas escolas públicas e particulares. Modelos de regressão logística, desenvolvidos para as variáveis turbidez, Escherichia coli, coliformes totais e parasitas intestinais não puderam ser relacionados a fatores singulares que explicassem riscos de comprometimento da água de consumo e de infecção com parasitas em crianças. Os problemas detectados, entretanto, podem ser ligados às condições precárias da infra-estrutura pública de abastecimento e das instalações sanitárias e sua manutenção nos domicílios. Técnicas de geoprocessamento foram aplicadas com sucesso para a elaboração de planos de informação espaciais, utilizados na geração dos modelos de regressão logística e no mapeamento de risco com base nos coeficientes da regressão logística.